Nanofabrication of Silicon Carbide and Optical Processing and Inspection of Noncurved Mirrors - Zuocai Dai; Sha Zhou; Tongguang Yang; Lihong Zou (Advances in Materials Science and Engineering)
With the gradual development of modern technology, there are still areas that need to be broken through in the field of science. In today’s society, the application range of noncurved mirrors is becoming more and more extensive. The application of aspheric mirrors will not only improve the imaging quality in all aspects but also improve the application of aspheric surfaces in aerospace, military, optics, physics, etc., and enhance economic benefits. Silicon carbide materials can be used in combination with noncurved mirror materials and produced in the market. This paper mainly studies how to prepare silicon carbide nanomaterials and discusses the relevant characteristics of silicon carbide through the preparation of silicon carbide materials. The aspheric mirror is mainly based on the large-diameter, high-precision aspheric mirror manufacturing system as the research background, which provides certain work experience for the follow-up research. Through the background research of the optical system of the aspheric mirror, this paper analyzed the essentials of aspheric processing technology and then combined the related content of the silicon carbide nanometer and the aspheric mirror. Nowadays, with the development of science and technology, the development prospects of silicon carbide nanomaterials are also more and more broad. After the entire production line of silicon carbide material was put into the production line, it has been recognized by the market, and the benefits are very good, bringing great production benefits to people, and it can be produced on a large scale in the future.